2008
DOI: 10.1098/rspb.2007.1661
|View full text |Cite
|
Sign up to set email alerts
|

Early Eocene lagomorph (Mammalia) from Western India and the early diversification of Lagomorpha

Abstract: We report the oldest known record of Lagomorpha, based on distinctive, small ankle bones (calcaneus and talus) from Early Eocene deposits (Middle Ypresian equivalent, ca 53 Myr ago) of Gujarat, west-central India. The fossils predate the oldest previously known crown lagomorphs by several million years and extend the record of lagomorphs on the Indian subcontinent by 35 Myr. The bones show a mosaic of derived cursorial adaptations found in gracile Leporidae (rabbits and hares) and primitive traits characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 16 publications
2
43
0
1
Order By: Relevance
“…The failure of amplification of RELIK-gag from Ochotona is in accordance with divergence times estimated by Katzourakis et al (8), which imply that the RELIK insertion into the leporid ancestor must be largely posterior to the Ochotona-Leporidae split (35 My or 40 to 50 My ago, according to molecular [8] or fossil [9] data, respectively). The presumed absence of RELIK-related sequences in pikas was furthermore supported by the fact that intensive screening of the WGS trace archives representing a twofold coverage of the genome of Ochotona princeps (project 19235) did not reveal a single sequence remotely similar to RELIK.…”
supporting
confidence: 63%
“…The failure of amplification of RELIK-gag from Ochotona is in accordance with divergence times estimated by Katzourakis et al (8), which imply that the RELIK insertion into the leporid ancestor must be largely posterior to the Ochotona-Leporidae split (35 My or 40 to 50 My ago, according to molecular [8] or fossil [9] data, respectively). The presumed absence of RELIK-related sequences in pikas was furthermore supported by the fact that intensive screening of the WGS trace archives representing a twofold coverage of the genome of Ochotona princeps (project 19235) did not reveal a single sequence remotely similar to RELIK.…”
supporting
confidence: 63%
“…Despite the wide expansion of these species, several endemic taxa are threatened to some degree, including Pronolagus , Bunolagus , Romerolagus , Nesolagus , Pentalagus , Caprolagus , and some species of Sylvilagus and Lepus [1]. Fossil records from Western India indicated an Asia origin of lagomorphs, which was dated to the early Eocene [18]. The sister relationship of ochotonids and leporids is widely accepted; however, it is unclear how their distribution ranges differentiated during evolution, and what drove their disparate evolutionary process.…”
Section: Introductionmentioning
confidence: 99%
“…this sequence fragment has been evolving under positive selection. The occurrence of this nucleotide pattern in the three Ochotona species studied in this work and its absence in the other lagomorphs, suggests that this evolutionary event happened before the radiation of the Ochotona genus (between 6 and 20 mya) [39] and after the split of Ochotonidae and Leporidae families (between 31 and 65 mya) [36-38]. …”
Section: Discussionmentioning
confidence: 99%
“…McKenna and Bell [34] and Asher et al [35] suggested that the families’ separation occurred around 37 my ago. Three other authors [36-38] suggested 65 my as the leporid-ochotonid divergence time. These different molecular dating models of leporid-ochotonid separation were used by Lanier and Olson [39] to infer a common ancestor for pikas.…”
Section: Introductionmentioning
confidence: 99%